Retrospective Analysis of Psychological Factors in COVID-19 Outbreak Among Isolated and Quarantined Agricultural Students in a Borneo University - Muhamad, Assikin Bin; Pang, Nicholas Tze Ping; Salvaraji, Loganathan; Rahim, Syed Sharizman Syed Abdul; Jeffree, Mohammad Saffree; Omar, Azizan (Frontiers in Psychiatry, 2021)
Introduction: Much has been known about the psychological issues that can emerge in people who are unable to move freely and quarantined. COVID-19 pandemic has no contrast from previous outbreaks like SARS and MERS that ensue worries and boost anxiety level. This article seeks to examine the unique psychological changes that occur in students who have been quarantined inside university campus and assess sociodemographic factors associated with certain psychological factors. Methodology: The data was collected from students in Agricultural Campus. In first phase, the factor structure of the modified National Index Psychological Wellness (NIPW) as acceptable and to establish statistical parameters for validation, an exploratory factor analysis was done. In the second phase, Independent T-tests, ANOVA and Hierarchical Multiple regression were performed. Data were analysed using the Statistical Package for the Social Sciences (SPSS) version 26.0. Result/Discussion: A total of 46 male and 76 female students enrolled in this study. The Barlett’s test of sphericity was significant (p<0.001) and the Kaiser–Mayer–Olkin measure of sampling adequacy for the AUDIT-M was 0.901. Cronbach alpha of the entire modified NIPW was 0.657 which suggests reasonable internal consistency and subscales between 0.913-0.924. Raw scores of 12 positive items were higher for the quarantined group except for I can do daily routines, I understand what happens and I understand the action that is performed is fair. Raw mean scores of 8 negative scoring items were higher in the quarantined group, except for “I feel angry” (2.88 vs 2.89 for non-quarantined group). There were statistically significant differences between year groups for question I understand what happens, I understand the action that is performed is fair and I think everyone is good. Conclusion: Movement control order or compulsory quarantine orders can be distressing and may cause understandable psychological sequelae. Holistic management of a quarantine centre that addresses the needs and health of an individual student will give a positive impact on psychological wellness. Quarantining facilities can be a place of positivity, allowing people to live a shared experience together, provide peer support for each other, and give each other hope.